228Relationship of pesticide exposure with kidney function in NHANES: lessons from low level chronic exposure. (2nd September 2021) - Osborne, Nicholas; Reid, Simon; Karatela, Shamshed; Assefa, Yibeltal; Wan, En-Tzu Grace
Abstract: Background: Exposure to pesticides has been linked to many health outcomes. More recently, chronic kidney disease not related to diabetes or hypertension (CKDu) has been postulated to be related to rural occupational exposures in agricultural workers in several Low to Middle Income Country (LMIC) regions such as Mesoamerica and the Subcontinent. Our study wished to examine the relationship between pesticide exposure and kidney function. Methods: We used the resources of pooled population from NHANES 2001-2004, 2007-2010 (n = 29, 053). We examined pesticide exposure (logged, continuous) with kidney function as measured by glomerular filtration rate (derived from urinary creatinine) with and without presence of hypertension and diabetes. Logistic regression was adjusted for a range of cofactors such as age, sex, SES, tobacco, and heavy metals. Cadmium was used as a positive control. Results: Pesticides 2, 4-D, chlorpyrifos, malathion and 3-phenoxybenzoic acid (the major metabolite of deltamethrin) were associated with the increasing risk of kidney dysfunction (not with hypertension or diabetes) after adjusting for a range of known risk factors (OR 1.80 (1.47-2.21); 2.16 (1.57-2.98); 1.20 (0.94-1.54) and 1.40 (1.19-1.64), respectively). Cd was not associated with kidney dysfunction (OR 0.99 (0.81-1.21)), or acephate (OR 0.43 (0.13-1.48)). Conclusions: Chronic or acute pesticide exposure may increase the risk of kidney dysfunction, which is not related to hypertension or diabetes in particular. It may have a different pathological pathway from heavy metal exposures and CKD. This has repercussions for interventions in LMIC agricultural practices. Key messages: Pesticides are associated with kidney dysfunction not related to hypertension and diabetes.